Dynamically vulcanized EPDM/PP (40/60) blends - (:unkn) unknown (My University, 2006)
Dynamically vulcanized thermoplastic elastomer (TPE) blends were first described by Fisher. In the 1960s, the usage of TPE was low. However, the consumption of TPE is increasing today. Due to hard and soft polymer phases in its structure, TPE replaced a lot of materials. TPE materials are preferred today due to their good thermal properties, oxidation resistance, transparency, adhesion, compatibility with other polymers etc. As a result of the studies that were done in 1975, TPV - vulcanized thermoplastic elastomers were developed. In this study, TPV elastomers were produced by forming crosslinks with peroxide from different ratios, of EPDM and PP. Mixing was done with twin screw extruder. After that yield and tensile strength, the modulus of elasticity, % elongation, Izod impact strength, hardness, Melt Flow Index (MFI), Vicat Softening Point, Heat Deflection Temperature (HDT), and density of crosslinks were determined. Thermal transition temperatures and microstructure were determined with DSC and SEM, respectively. Copyright © Taylor & Francis Group, LLC.
Keywords: Dynamic vulcanization; Ethylene-propylene-diene terpolymer; Peroxide; Polypropylene; Thermoplastic elastomer